Sexual Harassment, Assault, and Rape: College Students Report Their Experiences - Madeline Yzurdiaga; Keisha E. Payne; Jerome Rabow (European Scientific Journal, ESJ, 2016)
This paper reviews current research regarding sexual harassment, assault, and rape and its consequences. We examine different populations in varied settings and at different ages. We supplement this analysis with personal vignettes from college students who recall how and when their harassment and assaults occurred. Their experiences are shown to affect their views on gender, and gender relations.